La responsabilidad precontractual de la administración, el principio de buena fe y el deber de información a postores - Morón Urbina, Juan Carlos (2019)
The present Essay analyzes the duty of the Administration to provide reliable, completeand truthful information to the bidders whom it calls to participate in a selectionprocess and also the consequences derived from the breach of this duty. In the sameway, this Essay analyzes the scope of the duty to be informed that the bidders havewhen applying for selection processes called by the public entities.